Comparison of the indentation strength and single-edge-v-notched beam methods for dental ceramic fracture toughness testing - Domingues, Natália Bertolo [UNESP]; Galvão, Beatriz Regalado; Ribeiro, Sebastião; Junior, Antonio Alves de Almeida; Longhini, Diogo [UNESP]; Adabo, Gelson Luís [UNESP] (Universidade Estadual de Campinas, 2016)
Aim: To study influence of the cooling rate after sintering a veneering porcelain (Vita VM9) on fracture toughness by indentation strength (IS) and single-edge-v-notched beam (SEVNB) methods. Methods: Vita VM9 bars were sintered according to the manufacturer's recommendation and cooled under three conditions: Slow (inside the furnace from sintering temperature to room temperature); Normal (inside the furnace from sintering temperature to 500 °C and outside the furnace from 500 °C to room temperature); and Fast (outside the furnace from sintering temperature to room temperature). Fracture toughness was measured by IS (n=10) and SEVNB (n=10) methods. Data were analyzed by two-way ANOVA (a=0.05). Results: The fracture toughness obtained from SEVNB (slow - 1.02±0.10; normal - 1.09±0.13; and fast - 1,02±0.18 MPa.m1/2 cooling techniques) was significantly lower than IS (slow - 1.19±0.13; normal - 1.17±0.07; and fast - 1.16±0.06 MPa.m1/2 cooling techniques). There was no significant influence of the cooling technique (p=0.012). Conclusions: The measurement technique influenced the fracture toughness values . IS method overestimated the fracture toughness values. Irrespective of the measuring method, cooling rate did not influence the Vita VM9 veneering porcelain fracture toughness.
Keywords: Ceramics; Dental materials; Mechanical processes